2008
DOI: 10.1519/jsc.0b013e31816a5ee4
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Type Composition and Capillary Density in Relation to Submaximal Number of Repetitions in Resistance Exercise

Abstract: The purpose of this study was to investigate the relationship between skeletal muscle fiber type composition and the maximum number of repetitions performed during submaximal resistance exercise. Twelve young men performed a maximum repetitions test at 85% of 1 repetition maximum (1RM) in the leg press, which was repeated after 1 week. Seven days after the second 85% 1RM test, they performed a maximum repetitions test at 70% of 1RM in the leg press. This test, at 70% 1RM, was repeated 7 days later. One week be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 25 publications
1
37
1
Order By: Relevance
“…A relationship has been shown to exist previously between capillary density and the number of submaximal leg press repetitions to exhaustion, suggesting that a high capillary density positively affects endurance performance (Terzis et al, 2008). However, we did not observe any reduction in the capillary density (cap/mm 2 ) following the 8‐day unloading period.…”
Section: Discussionmentioning
confidence: 87%
“…A relationship has been shown to exist previously between capillary density and the number of submaximal leg press repetitions to exhaustion, suggesting that a high capillary density positively affects endurance performance (Terzis et al, 2008). However, we did not observe any reduction in the capillary density (cap/mm 2 ) following the 8‐day unloading period.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, as no difference was found for the electromyographic parameters, peripheral factors may have influenced fatigue resistance [10, 15]. For example, Terzis et al [15] found a significant correlation (r = 0.70; P = 0.01) between the MNR at 70% 1RM in leg press and capillary density in vastus lateralis cross sectional area in twelve physically activity males.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Terzis et al [15] found a significant correlation (r = 0.70; P = 0.01) between the MNR at 70% 1RM in leg press and capillary density in vastus lateralis cross sectional area in twelve physically activity males. Thus, while Terzis et al [15] did not compare aerobic trained subjects, it is possible to presume that a higher capillary density in runners can lead them to a better ability to extend performance into strength endurance sets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations